Engineering Education, Innovation, and Economic Growth: A Case Study - Wai, Cai; Jusoh, Sufian; Radin A Rahman, Siti Aishah; Wang, Si Ya (International Journal of Engineering Pedagogy (iJEP), 2025)
The role of engineering education is pivotal in driving regional economic expansion, especially in the context of wider development strategies. The research investigates the connection between engineering-oriented tertiary education and technological advancements, utilizing panel data from Shanghai (2014–2023). Shanghai, as China’s economic center, serves as the focal point of this study. The study investigates the role of regional innovation in bridging the gap between education and economic expansion, serving as a crucial link. The study underscores the intricate interplay among education, innovation, and economic growth, underscoring the significance of strategic investments and partnerships between industry and universities. Research indicates that merging educational elements with innovative approaches promotes industrial advancement and enduring economic development, potentially extending its impact beyond Shanghai to influence worldwide regional economies.